Typification of the name Memecylon talbotianum Brandis (Melastomataceae) - Das Das, Moumita; Maity, Debabrata; Pramanik, Arabinda (Phytotaxa, 2015)
The lectotype of the Indian Memecylon talbotianum Brandis is designated here.